Coloured Petri Nets Extended with Channels for Synchronous Communication - Christensen, Søren; Hansen, Niels Damgaard (DAIMI Report Series, 1992)
This paper shows how Coloured Petri Nets (CP-nets) can be extended to support synchronous communication. We introduce typed communication channels through which transitions are allowed to communicate. Small examples show how channel commnunication is convenient for creating compact and comprehensive models. The concepts introduced in this paper originate from the practical use of Petri nets for modelling, and they are formally defined in such a way that they preserve the basic properties of CP-nets. We show how a CP-net with channels can be transformed into a behaviourally equivalent CP-net. This allows us to deduce properties of CP-nets with channels from well-known properties of CP-nets. As an example,we extend the concept of place invariants to cope with CP-nets with channels and show how place invariants can be found. This is done without transforming the CP-nets with channels into their equivalent CP-nets. CP-nets with channels can be used as a basis for new hierarchy constructs, and we outline an alternative to invocation transitions, based on CP-nets with channels. The reader is assumed to be familiar with the notion of CP-nets.